2010
DOI: 10.1111/j.1526-4637.2010.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Provocation Technique for Adolescents with Chronic Pain: Preliminary Evidence for Its Effectiveness

Abstract: Results are discussed in terms of the importance of focused treatment strategies such as interoceptive exposure for adolescents suffering from disabling chronic pain. Future studies are warranted to carefully investigate the effectiveness and possible process of change during the PPT such as sensory, cognitive, emotional, and memory aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…At this stage, 5 studies that reported on overlapping samples were identified. [36][37][38][39][40] We decided to include articles that first presented results on the respective samples, or articles that presented new aspects (eg, assessment of additional outcomes) into the present review. An additional article with lack of treatment description and outcome data also was excluded.…”
Section: Results Of Searchmentioning
confidence: 99%
“…At this stage, 5 studies that reported on overlapping samples were identified. [36][37][38][39][40] We decided to include articles that first presented results on the respective samples, or articles that presented new aspects (eg, assessment of additional outcomes) into the present review. An additional article with lack of treatment description and outcome data also was excluded.…”
Section: Results Of Searchmentioning
confidence: 99%
“…This published systematic review integrated results from ten studies and had a strong focus on the outcomes of chronic pain treatment. In this review, we concentrated more on providing a comprehensive description of existing specialized rehabilitation programs and therefore further included referenced studies that were excluded from the systematic review, for example due to overlapping samples [25,37,38,39,40,41,42]. Additionally, we identified five more recent studies on this topic through a nonsystematic search in Medical Literature Analysis and Retrieval System Online (MEDLINE) and by conducting a manual search [16,28,34,43,44,45].…”
Section: Methodsmentioning
confidence: 99%
“…Interoceptive exposure to painful and other anxiety-provoking bodily sensations has also been suggested to reduce anxiety sensitivity as well as pain-related anxiety (113). Preliminary research with pediatric populations suggests that when interoceptive exposure (in addition to bilateral tactile stimulation and imagery involving adolescents' use of coping strategies) was used as an adjunct to standard multimodal treatment, it resulted in lower pain intensity and similar reductions in pain-related disability among adolescents with chronic pain (114). parent-child/adolescent factors and treatment: Given the integral role of family in children and adolescents' pain experience, parent behavioural training is often incorporated into evidence-based psychological treatments for pediatric chronic pain.…”
Section: Treatmentmentioning
confidence: 99%